Interoperability Business Process Contending Cultural Barrier to Prepare Competitive Human Resources - Hidayat, Safril; Legionosuko, Tri (International Journal of Psychosocial Rehabilitation, 2020)
Human resources are a comparative advantage possessed by Indonesia. However, a large number of human resource has not been accompanied by adequate quality to face the dynamics and complexity of the strategic environment, science and technology development, and Industrial revolution 4.0. In realizing competitive human resources, a comprehensive and integral interoperability business process is needed between various national government institutions therefor synergy will be established and breaking down all cultural barriers to raise high quality human resources. On the other hand cultural barriers strongly affect organizational change that is contended the interoperability business process so that the preparation of superior human resources runs slowly. This research uses qualitative research methods with literature study. The results show that superior human resources can be emerged by transforming role of each institutions orchestrated on the basis of information and technology within creative cooperation. Indicators of human resources prepared by the state to create high quality human resources require synergy between government agencies. Leading sector must be appointed by the government by establishing supra organization above ministry so that the realization of high quality human resources is in accordance with the indicators or criteria needed so that the preparation of human resources can be done in a measurable and sustainable manner in projecting demographic bonus in the future .